KEPENTINGAN INDONESIA MENANDATANGANI PERJANJIAN INDONESIA-UNITED ARAB EMIRATES COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IUAE-CEPA) - Salsabila, Domoynique; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to analyze and explain Indonesia's interests behind the signing of an agreement on comprehensive economic cooperation with the United Arab Emirates (IUAE-CEPA). The Comprehensive Cooperation Agreement requires long and detailed discussions between Indonesia and the United Arab Emirates and has binding results between the two. Therefore, it is important for us to see what underlies Indonesia's desire to continue to go through the process and sign it. The method used in this research is a qualitative research method. This qualitative research method has the characteristics of understanding, explaining and describing the circumstances of a fact. The author will then use descriptive analysis research methods to examine research problems. The author used descriptive qualitative research because it was deemed appropriate to explain the problems studied, namely to provide exposure and explanation regarding Indonesia's interests in signing the IUAE-CEPA agreement. The 1945 Constitution, paragraph 4, shows the direction of Indonesia's national interests, which generally refer to the goals and priorities of the state that are important for security, prosperity and welfare. There are 4 main components of Indonesia's national interests, namely sovereignty, economy, security and environment. Looking at the points of the IUAE-CEPA cooperation that have been agreed upon, Indonesia's interests in signing the IUAE-CEPA agreement lean towards economic interests. The economic interests in question focus on Indonesia's efforts to expand its market and Indonesia's interests in opening up greater investment from the United Arab Emirates. Keywords: IUAE-CEPA, Comprehensive, Importance, Export,Investment